In a triangle A B C , cot A + cot B + cot C = 3 . Find the nature of the triangle.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let's use cot A = 3 / 3 , it appears to be fitting. The previous is also 1 / 3 rationalized, so we draw a triangle and see that the 1 must be the adjacent side of the angle, and 3 the opposite side of the angle c o t A . By the Pythagorean theorem, the hypotenuse is 2 and with this we know that the angle A is 6 0 d e g r e e s OR π / 3 .
So, if a triangle has the angles A , B , C each of equal length, π / 3 in this case, then it is equilateral
Given cot A + cot B + cot C = 3
OkaY now since the A,B,C are the angles of a triangle so the sum of angle of any triangle is equal to 180°
tan ( A + B + C ) = 0
Therefore ,
tan A + tan B + tan C = tan A × tan B × tan C
We came to this result by using the formula tan ( A + B + C ) = 1 − ( tan A × tan B × tan C ) tan A + tan B + tan C − tan A × tan B × tan C
Now , Dividing by tan A × tan B × tan C Both sides of equation tan A + tan B + tan C = tan A × tan B × tan C We get ( cot A × cot B ) + ( cot B × cot C ) + ( cot C × cot A ) = 1
Squaring both sides of the equation
cot A + cot B + cot C = 3 We get cot 2 A + cot 2 B + cot 2 C + 2 × ( ( cot A × cot B ) + ( cot B × cot C ) + ( cot C × cot A ) ) = 3
Therefore , cot 2 A + cot 2 B + cot 2 C = 1
Now using the inequality , ( x 2 + y 2 + z 2 ) ≥ ( x y + y z + z x )
Now multiplying both sides by two and adding x 2 + y 2 + z 2
We get
3 ( x 2 + y 2 + z 2 ) ≥ ( x + y + z ) 2
Substitute x = cot A
, y = cot B
and z = cot C
We get 3 ( cot 2 A + cot 2 B + cot 2 C ) ≥ ( cot A + cot B + cot C ) 2
As we substitute the values of ( cot 2 A + cot 2 B + cot 2 C )
and cot A + cot B + cot C
We get to know that the equality holds ,
This implies
cot A = cot B = cot C
Therefore we get ,
A = B = C = 3 π
So the answer is equilateral triangle.
P.S : Please share your ideas about representing the answer.
Bonus : Prove the inequality that I have used.
Problem Loading...
Note Loading...
Set Loading...
For △ A B C , tan A + tan B + tan C = tan A tan B tan C , ⟹ cot A cot B + cot B cot C + cot C cot A = 1 . Now we have:
cot A + cot B + cot C cot 2 A + cot 2 B + cot 2 C + 2 ( cot A cot B + cot B cot C + cot C cot A ) cot 2 A + cot 2 B + cot 2 C + 2 ( 1 ) cot 2 A + cot 2 B + cot 2 C cot 2 A + cot 2 B + cot 2 C = 3 = 3 = 3 = 1 = cot A cot B + cot B cot C + cot C cot A Squaring both sides
The last equation above is satisfied when A = B = C , hence △ A B C is an equilateral triangle .